Recent advances in process improvement of dark fermentative hydrogen production through metabolic engineering strategies - Krishnan, Santhana; Kamyab, Hesam; Mohd, Nasrullah; Zularisam, A. W.; Yadav, Krishna Kumar; Reungsang, Alissara; Chaiprapat, Sumate (Elsevier, 2023)
Biological means of hydrogen (H2) production has attracted tremendous research and development attention. Dark fermentation provides a possible way of producing H2 from a range of renewable energy sources, including wastewater. During fermentation, various metabolites are formed to create a complex metabolic flux network. Insufficient focus has been placed on the metabolic engineering that is intrinsic to fermentation. This current review summarizes the biochemical pathways occurring in the metabolic network of dark fermentation and how the key operational factors influence metabolism during dark fermentation. Recent developments and strategies for metabolic engineering that have been described to enhance H2 production are recommended. Finally, the economic analysis related to bio-H2 production and prospects is examined. It is envisaged that this study can give beneficial aspects in terms of fundamental knowledge, understanding, and the latest technology for scientists and research engineers in the field of bio-based H2 generation.